2022
DOI: 10.1111/jipb.13384
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of phytohormones and epigenetic regulation: A recipe for plant development and plasticity

Abstract: Both phytohormone signaling and epigenetic mechanisms have long been known to play crucial roles in plant development and plasticity in response to ambient stimuli. Indeed, diverse signaling pathways mediated by phytohormones and epigenetic processes integrate multiple upstream signals to regulate various plant traits. Emerging evidence indicates that phytohormones and epigenetic processes interact at multiple levels. In this review, we summarize the current knowledge of the interplay between phytohormones and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 231 publications
0
7
0
Order By: Relevance
“…There are abundant causal tests of DNA methylation's effect on plasticity in plants. More than a decade of research interrogating A. thaliana DNA methylation using chemical DNMT inhibitors or epiRILs have demonstrated effects on the plasticity of growth, morphometrics, and flowering time across nitrogen, salinity, and nutrition levels ( Bossdorf et al 2010 ; Boyko et al 2010 ; Zhang et al 2013 ; Jiang et al 2023 ). Similar experiments in non-model plants including angiosperms and bryophytes have detected significant effects of DNA methyltransferase inhibition on plastic responses to intraspecific competition ( Puy et al 2018 ), salinity ( Arya et al 2016 ), transplantation ( Sammarco et al 2022 ), and iron deficiency ( Sun et al 2021 ).…”
Section: Observations At the Organismal Level—causal Tests Of Epigene...mentioning
confidence: 99%
“…There are abundant causal tests of DNA methylation's effect on plasticity in plants. More than a decade of research interrogating A. thaliana DNA methylation using chemical DNMT inhibitors or epiRILs have demonstrated effects on the plasticity of growth, morphometrics, and flowering time across nitrogen, salinity, and nutrition levels ( Bossdorf et al 2010 ; Boyko et al 2010 ; Zhang et al 2013 ; Jiang et al 2023 ). Similar experiments in non-model plants including angiosperms and bryophytes have detected significant effects of DNA methyltransferase inhibition on plastic responses to intraspecific competition ( Puy et al 2018 ), salinity ( Arya et al 2016 ), transplantation ( Sammarco et al 2022 ), and iron deficiency ( Sun et al 2021 ).…”
Section: Observations At the Organismal Level—causal Tests Of Epigene...mentioning
confidence: 99%
“…These key genes in GA biosynthesis and signaling pathway are regulated by epigenetic mechanisms. It has been demonstrated that DELLA protein regulates GA, brassinosteroid and jasmonic acid pathways by histone deacetylation to adjust plant growth and development [ 47 , 48 ]. DELLA displayed a higher expression level in PA-F than that in PA-M at S2, indicating that the DELLA proteins suppress nutritional and reproductive growth [ 23 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, melatonin enhances thermotolerance in soybean seedlings through balancing redox homeostasis, orchestrating antioxidant defense, and modulating phytohomones and osmolytes biosynthesis ( Imran et al., 2021 ). Meanwhile, phytohormones can reciprocally modulate epigenetic processes and regulate gene expression via other transcriptional regulatory pathways ( Jiang et al., 2023 ). Therefore, untangling the complex crosstalk existing among phytohormones, stress signalling molecules and osmolytes will crucially assist in pinpointing key hub points or nodes for targeted manipulation for metabolic engineering of D/+H tolerance in crops ( Lv et al., 2018 ; Jogawat, 2019 ; Jogawat et al., 2021 ; Saddhe et al., 2021 ; Sun et al., 2021 ; Yaqoob et al., 2022 ).…”
Section: Key Pathways Targeted For Manipulationmentioning
confidence: 99%
“…Therefore, untangling the complex crosstalk existing among phytohormones, stress signalling molecules and osmolytes will crucially assist in pinpointing key hub points or nodes for targeted manipulation for metabolic engineering of D/+H tolerance in crops ( Lv et al., 2018 ; Jogawat, 2019 ; Jogawat et al., 2021 ; Saddhe et al., 2021 ; Sun et al., 2021 ; Yaqoob et al., 2022 ). Additionally, a comprehensive understanding of the common features of plant transcriptional- and epigenetic-regulatory pathways and how cross-regulation among phytohormones acts upon gene expression will be key in identifying hub target genes (such as CPKs and MPKs) for engineering D/+H tolerance ( Waadt et al., 2022 ; Jiang et al., 2023 ; Yin et al., 2023 ). However, it must be highlighted that engineering phytohormone signalling pathways is challenging and delicate, due to the large genetic redundancy and complexity of the signalling pathways ( Braguy and Zurbriggen, 2016 ).…”
Section: Key Pathways Targeted For Manipulationmentioning
confidence: 99%